Etanercept in axial spondyloarthritis – treatment efficacy - I. Z. Gaydukova; O. V. Inamova; R. R. Samigullina; A. L. Chudinov; A. S. Bychkova (Научно-практическая ревматология)
The beginning of the 21st century was marked by a simultaneous changes in view on pathogenesis, diagnostics and treatment of axial spondyloarthritis (axSpA). Anti-TNFα inhibitors were the first biologics prescribed in axSpA. 20 year after the biological treatment was first prescribed we have enough data to understand their long-term efficacy.The aim of this study is to evaluate the long-term efficacy of etanercept in patients with axial spondyloarthritis based on data published in periodicals and clinical practice.Patients and methods. An analysis of publications from medical database and data from the St. Petersburg register of patients with rheumatic diseases (n=68) was performed to assess the effectiveness of etanercept in axSpA treatment in the long-term perspectives. Descriptive statistics methods were used.Results. In clinical studies and in real word practice, etanercept has shown high efficiency in reducing clinical, laboratory and visual manifestations of non-radiographic and radiographic axial spondyloarthritis at early and advanced stages of their development.Conclusions. In the long term, the use of etanercept is associated with an increasing slowdown in structural progression while maintaining a stable clinical and laboratory improvement. Discontinuation of treatment in the majority of patients leads to exacerbation of axSpA. At the same time, the low immunogenicity of etanercept allows the resumption of axSpA treatment with a high probability of re-achieving the lost effect with a low probability of secondary ineffectiveness or anaphylaxis.